Biosynthesis of chondroitinase and hyaluronidase by different strains of Paracoccidioides brasiliensis - Assis, C. M. de; Gandra, R. F.; Gambale, W.; Shimizu, M. T.; Paula, C. R. (Microbiology Society, 2003)
The biosynthesis of chondroitinase and hyaluronidase by different isolates of Paracoccidioides brasiliensis was investigated in 20 strains isolated from patients (17 strains), a penguin (Pygocelis adeliae, one strain), an armadillo (Dasypus novemcinctus, one strain) and the environment (dog food, one strain). All the P. brasiliensis isolates studied had the ability to produce chondroitinase and hyaluronidase, although differences in colony morphology and enzyme production were detected among them. These results suggest that further investigations should be carried out in the clinical field in order to clarify the potential role of P. brasiliensis enzyme production in the pathogenesis of paracoccidioidomycosis.
Keywords: hyaluronidase; n acetylgalactosamine 4 sulfatase; armadillo; bacterial strain; bacterium isolate; bacterium isolation; biosynthesis; controlled study; dog; electric potential; enzyme synthesis; nonhuman; Paracoccidioides; Paracoccidioides brasiliensis; pathogenesis; penguin; priority journal; South American blastomycosis; Animal Feed; Animals; Armadillos; Birds; Chondroitin ABC Lyase; Humans; Hyaluronoglucosaminidase; Paracoccidioidomycosis; Virulence